Theoretical evaluation of various configurations of silica membrane reactor in methanol steam reforming using CFD method. (4th March 2020) - Ghasemzadeh, K.; Jafar Harasi, N.; Iulianelli, A.; Basile, A.
Abstract: The main purposes of this work was to evaluate from a theoretical point of view the performance of silica membrane reactors (MRs) in various configurations for generating hydrogen via methanol steam reforming (MSR) reaction using a two dimensional computational fluid dynamic (CFD) method, presenting details about molar fractions of gas species, velocity and pressure distributions at the simulated conditions. The CFD model was firstly validated and, then, used for the simulations, achieving an acceptable agreement between numerical outcomes and experimental data. The simulations were realized for MSR reaction carried out in three types of silica MRs, namely: 1) silica MR with cocurrent flow pattern (MR1); 2) silica MR with countercurrent flow pattern (MR2); 3) silica MR with countercurrent flow pattern including a water gas shift (WGS) reaction stage in the permeate side (MR3), meanwhile comparing the results with a traditional reactor (TR). The influence of several operating parameters (reaction temperature and pressure, and feed flow rate) on the performance of the aforementioned silica MRs in terms of methanol conversion, hydrogen yield and CO-selectivity was evaluated and the results compared with an equivalent TR. The simulations via CFD method indicated the MR3 results to be the best solution over the other MR proposed configurations and the TR as well, presenting the best simulation results at 10 bar of transmembrane pressure, 513 K, SF = 6, GHSV = 6000 h −1 and feed molar ratio = 3/1 with CO selectivity ≤0.04%, methanol conversion and hydrogen yield >90%. Highlights: A CFD-based model was used to simulate silica MR performance during MSR reaction. At 513 K, GHSV = 6000 h −1, S/MeOH = 3/1, the best results were obtained. As best results, CO selectivity ≤0.04%, methanol conversion and H2 yield >90%. In all simulation cases, the silica MR shows better performance over to the TR. In all cases, silica MR3 indicates better performances over to other cases.